Mythic migrations: Recreating migrant histories in Canadian fiction - Mullen, Amanda (University of Ottawa (Canada), 2005)
This thesis examines the work of five Canadian writers who use their fiction to recreate an immigrant past and to mythologize an originary moment in Canada: a migrant's arrival and settlement in a new land. Mordecai Richter's Solomon Gursky Was Here (1989), Sky Lee's Disappearing Moon Cafe (1990), Jane Urquhart's Away (1993), Lawrence Hill's Any Known Blood (1997), and Nino Ricci's trilogy, Lives of the Saints (1990), In a Glass House (1993), and Where She Has Gone (1997) each express a nostalgic longing for an authenticating mythology that will give a previously silenced ethno-cultural group a place in the national narrative. Nostalgia literally means a painful return home, and the narrators of these novels express a bittersweet longing for a Canadian past, for a Canadian home. While nostalgia has traditionally played a central role in ethnic literature, this longing has typically rested on a nostalgic desire to return to a distant homeland. Yet the narrators of this study express a nostalgia for a different kind of origins---for origins in a new land. Richter, Lee, Urquhart, Hill, and Ricci create detailed genealogies in their novels that show how their different groups---Jewish, Chinese, Irish, Black, and Italian---helped build the nation and what roles each of these groups played in Canada's past. This thesis thus reveals that the interrogation of Canada's master narratives is not complete and that, even for later generations of immigrants, there remains a desire to establish their identities as Canadian The five writers of this study are deliberately challenging the authority of Canada's dominant cultural paradigm by recreating the immigrant experiences of their ethno-cultural groups in order to refute the myth of two founding nations and to establish Canada as home for their own particular groups. With their mythologized versions of history, these writers are striving to include neglected and forgotten voices in the story of Canada.
Keywords: Literature, Canadian (English).